Direct Profiling of Phytochemicals in Tulip Tissues and In Vivo Monitoring of the Change of Carbohydrate Content in Tulip Bulbs by Probe Electrospray Ionization Mass Spectrometry - Yu, Z. (2009)
Probe electrospray ionization (PESI) is a recently developed ESI-based ionization technique which generates electrospray from the tip of a solid needle. In this study, we have applied PESI interfaced with a time of flight mass spectrometer (TOF-MS) for direct profiling of phytochemicals in a section of a tulip bulb in different regions, including basal plate, outer and inner rims of scale, flower bud and foliage leaves. Different parts of tulip petals and leaves have also been investigated. Carbohydrates, amino acids and other phytochemicals were detected. A series of in vivo PESI-MS experiments were carried out on the second outermost scales of four living tulip bulbs to monitoring the change of carbohydrate content during the first week of initial growth. The breakdown of carbohydrates was observed which was in accordance with previous reports achieved by other techniques. This study has indicated that PESI-MS can be used for rapid and direct analysis of phytochemicals in living biological systems with advantages of low sample consumption and little sample preparation. Therefore, PESI-MS can be a new choice for direct analysis/profiling of bioactive compounds or monitoring metabolic changes in living biological systems. © 2009.